Hudožestvennoe ubranstvo cerkvej Valaamskogo monastryrâ XVII - načala XIX veka - Sipola, Olga (University of Jyväskylä, 2016)
The collection of church art of the Valamo monastery belongs to worthy rarities. Due to the evacuation from Karelia to Finland, collection survived almost complete. Despite the fact that the collection is well known to specialists in Finland and Russia, the research processes is just beginning. Especially little information exists about the icons of earlier period than of the 18th century. Almost nothing is known about the number of them, neither origins nor something about the painters of them. Many icons of the 18th century from the Valamo’s collection decorated the monastery churches. For this reason, the focus of this dissertation is the decoration of the main interiors of the Cathedral of Transfiguration and the church of Uspenie in Ladoga’s Valamo. The objects of this research are the components of the icon painting of the churches, their present condition, iconography and style. According the archives and monastery’s church descriptions from the 18th and 20th centuries it was possible to reconstruct the altar wall’s – iconostasis, the main features of their architectural decoration and the separate icons. In similar way I reconstructed church’s columns and walls and their icons. On the bases of concrete research in the archives and in praxis, and on applied theories I proposed the hypotheses about the general ideas, the topics and the programmes of the decoration of church interiors. The investigation based on the theoretical sources of the Vienna-school and empiric methods used by the Russian researchers of art history. Different methods were used, including iconographical and style analysis, and historical reconstruction, philology and semiotic as methods of survey. More than a hundred icons and one drawing were studied and a scientific catalogue was made. According the monastery’s archives the icons were dated and some icon painters were identified by the style of Lake Ladoga’s area, Yaroslavl and Tver. The reconstruction revealed that the main idea of the Transfiguration cathedral and the Uspenie ...